The Effect of Group and Individual Sports Activities on the Quality of Life of Elderly Women with two Optimistic and Pessimistic Cognitive Styles - Ramina Atashgahian; Mehdi Shahbazi; Reza Rostami; Elahe Arabameri (پژوهش‌های کاربردی روانشناختی, 2025)
The objective of the present research was to elucidate the quality of life and sports activity of geriatric women aged 65 to 75 who exhibit two cognitive styles: optimistic and pessimistic. It has been conducted with both optimism and pessimism. The current research was semi-experimental in nature, with a pre-test-post-test design, and was applied in terms of purpose. The statistical population of the research included elderly women aged 65 to 75 who resided in Tehran city in 2023. The sample includes 40 elderly individuals who were randomly assigned to four experimental groups based on optimistic and pessimistic cognitive styles and group and individual sports activities. These individuals were selected using the available sampling procedure. The groups were subjected to eight sessions of aerobic exercise and strolling. The pre-test was administered prior to the intervention's implementation, while the post-test was administered subsequent to its conclusion. The World Health Organization quality of life questionnaire form 36 questions (SF-36) and Shearer and Carver optimism questionnaire were administered during the pre-test phase of this study. Subsequently, the groups were subjected to a walking and athletics intervention, and they engaged in aerobics. The data was analyzed using SPSS software version 27 and the composite variance analysis method. The composite variance analysis revealed a significant disparity in the quality of life between the training groups between the pre-test and post-test (P<0.05). Also, the quality of life of the elderly was enhanced in all categories as a result of the group and individual sports intervention. The results indicated that the quality of life of the optimistic groups was superior to that of the pessimistic group during the post-test stage. This investigation demonstrated that the elderly’s health and quality of life are enhanced by engaging in sports activities as a result of lifestyle modifications